In every generation - Blake, Kendare (Hyperion, 2022)
Every generation has their chosen one, and Frankie Rosenberg has some big shoes to fill. Her mom Willow, her aunt Buffy, and the original Scooby Gang destroyed the Hellmouth and saved the world from the First Evil all while they were teenagers. But Frankie is just trying to survive her sophomore year and use her budding magical powers to make the world a better place. When the slayer community is attacked and a new threat approaches Sunnyvale, Frankie must take up the mantle as the first ever Slayer-Witch and prevent the Hellmouth from opening again.